Evolutionary aspects of non-cell-autonomous regulation in vascular plants: structural background and models to study - Evkaikina, Anastasiia I.; Romanova, Marina A.; Voitsekhovskaja, Olga V. (Frontiers in Plant Science, 2014)
Plasmodesmata (PD) serve for the exchange of information in form of miRNA, proteins and mRNA between adjacent cells in the course of plant development. This fundamental role of PD is well established in angiosperms but has not yet been traced back to the evolutionary ancient plant taxa where functional studies lag behind studies of PD structure and ontogenetic origin. There is convincing evidence that the ability to form secondary (post-cytokinesis) PD, which can connect any adjacent cells, contrary to primary PD which form during cytokinesis and link only cells of the same lineage, appeared in the evolution of higher plants at least twice: in seed plants and in some representatives of the Lycopodiophyta. The (in)ability to form secondary PD is manifested in the symplastic organization of the shoot apical meristem (SAM) which in most taxa of seedless vascular plants differs dramatically from that in seed plants. Lycopodiophyta appear to be suitable models to analyze the transport of developmental regulators via PD in SAMs with symplastic organization both different from, as well as analogous to, that in angiosperms, and to understand the evolutionary aspects of the role of this transport in the morphogenesis of vascular plant taxa.